Patient Perception of Care, Outcomes, and Consequences from Placenta Accreta Spectrum: A Survey-Based Study - Shainker, Scott A.; Cornely, Ronald M.; Astake, Rebecca; Hacker, Michele R. (American Journal of Perinatology, 2022)
Objective Placenta accreta spectrum (PAS) is an obstetric diagnosis that carries significant risks. However, little is known about patient perceptions of care. This study was conducted to describe the patient experience, reported outcomes, and assess geographical variation in PAS care in the United States.Study Design Partnering with a PAS patient advocacy organization, we conducted an online survey of PAS patients. Perceptions of care and outcomes, and geographic variation were described.Results We received 108 responses (69% response rate); 103 respondents delivered in the United States. Demographic characteristics were similar across each region. Most (67%) reported at least one prior cesarean delivery and 53% reported placenta previa in the PAS pregnancy. Over half (63%) reported an antenatal suspicion of PAS and 66% of those respondents reported changing their delivery hospital as a result of their antenatal diagnosis. Though not statistically significant, both showed variability across regions (both p ≥0.60). Seventy-five percent of respondents with antenatal diagnosis reported their pregnancy was managed by a dedicated PAS care team, which did not differ by region (p = 0.80). A majority of respondents (75%) felt their PAS care team was prepared for their delivery; this too did not vary across regions (p = 0.97). Many respondents reported at least one physical (63%) or mental health (17%) adverse outcome as a result of their PAS pregnancy.Conclusion As reported by prior PAS patients, perception of care and outcomes are overall favorable. There are long-term physical and mental adverse consequences reported. Geographical variation is mixed, however, national guidelines are predominately followed.Key Points
Keywords: placenta accreta spectrum; patient perception; mental health; patient survey